Internet-of-Things (IoT) Systems : Architectures, Algorithms, Methodologies - Serpanos, Dimitrios Nikolaou; Wolf, Marilyn, 1958- (Springer, 2018)
This book covers essential topics in the architecture and design of Internet of Things (IoT) systems. The authors provide state-of-the-art information that enables readers to design systems that balance functionality, bandwidth, and power consumption, while providing secure and safe operation in the face of a wide range of threat and fault models. Coverage includes essential topics in system modeling, edge/cloud architectures, and security and safety, including cyberphysical systems and industrial control systems